Destabilising equilibriums: harnessing the power of disruption in participatory action research. Issue 3 (27th May 2019) - Cook, Tina; Brandon, Toby; Zonouzi, Maryam; Thomson, Louise
ABSTRACT: This article draws on insights gained from three projects described as participatory action research (PAR) undertaken in the UK. What binds them together is that each project coordinator raised the issue of the under-representation of opportunities for disruption in the possible trajectory to knowledge democracy. PAR places a relational process at the centre of the research practice. It brings together people with varied knowledges, perspectives and experiences and aspires to be a non-hierarchical, relational, collaborative endeavour. This challenges the traditional hierarchical hegemony of the external expert in research situations. Bringing people together does not, however, equate to shared agency, authentic participation and knowledge democracy. For different knowledges to be created previous knowledges need to be disrupted.The argument raised in this paper is that a neglected element of PAR has been the deliberate intent to nurture disruption within communicative spaces in relationally based engagements. It is posited that the disruption of beliefs and assumptions that underpin local actions, is an important enabler of other voices and knowledges being recognised and acted upon. The three projects described reveal how and why the harnessing of power through disruption contributes to creating a functional knowledge democracy for more radical change.